1988
DOI: 10.1039/an9881301453
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence enhancement of the europium(III)-thenoyltrifluoroacetone-trioctylphosphine oxide ternary complex by gadolinium(III) and its application to the determination of europium(III)

Abstract: A study of the enhancement of the fluorescence intensity of the Eulll -thenoyltrifluoroacetone (-A) -trioctylphosphine oxide (TOPO) system by Lalll, Gdlll, Lull1 and Ylll has been carried out in a colloidal-like suspension. Gadolinium(ll1) caused the largest enhancement of the fluorescence intensity. In the presence of this element the weak fluorescence of the Eulli-TTA -TOPO system was enhanced by a factor of about 18 at a pH of between 5.5 and 6.5. The excitation and emission wavelengths were 343 and 61 5 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 0 publications
1
29
0
1
Order By: Relevance
“…The ECL spectra in the presence of Eu(DBM) 3 phen and Eu(TTA) 3 phen, shown in Figs 5A and 5B, demonstrated that another maximum emission peak at about 610 nm also appeared at ECL-1, in addition to the maximum emission 530 nm for ECL-1 and ECL-2 in both systems. The emission of 610 nm was identical with fluorescent characteristic peaks of Eu(DBM) 3 2− was reduced to SO 4 •− , followed by the reaction with ligand radical dianions to generate nonemissive ligand-excited states, which then underwent intramolecular energy transfer to the Eu(III) f orbitals to form the excited states Eu(III)*. We proposed that the ECL mechanism at about 610 nm may also follow the ligand-sensitization mechanism.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…The ECL spectra in the presence of Eu(DBM) 3 phen and Eu(TTA) 3 phen, shown in Figs 5A and 5B, demonstrated that another maximum emission peak at about 610 nm also appeared at ECL-1, in addition to the maximum emission 530 nm for ECL-1 and ECL-2 in both systems. The emission of 610 nm was identical with fluorescent characteristic peaks of Eu(DBM) 3 2− was reduced to SO 4 •− , followed by the reaction with ligand radical dianions to generate nonemissive ligand-excited states, which then underwent intramolecular energy transfer to the Eu(III) f orbitals to form the excited states Eu(III)*. We proposed that the ECL mechanism at about 610 nm may also follow the ligand-sensitization mechanism.…”
mentioning
confidence: 85%
“…Eu(TTA) 3 phen was synthesized according to the following procedure. A mixture of 1.0 mmol EuCl 3 , 3.0 mmol TTA and 1.0 mmol phen was dissolved in 30 mL ethanol with a few drops of NaOH aqueous solution under vigorous stirring.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…Практическое применение колюминесцен-ции связано с определением ионов Eu 3+ [4] и Sm [5,6]. Методики отличаются низким пределом обнаружения…”
Section: T D Smirnova E a Zhelobitskaya T G Danilina N V Nunclassified
“…The triplet state energy level of the organic linkers, such as fumaric acid (24034 cm −1 ), is higher than the resonance energy levels of Tb 3+ (20430 cm −1 ), therefore, the energy absorbed by the ligand can effectively transfer to Tb 3+ , thus, the luminescence efficiency of Tb 3+ ions is enhanced [30]. When the rare earth complexes composed of active rare-earth ions Tb 3+ and inert rare-earth ions (La 3+ , Y 3+ and Gd 3+ ) were grown with some organic ligands, the characteristic emission bands of active rare-earth ions Tb 3+ were enhanced greatly.…”
Section: Energy-transfer Mechanismmentioning
confidence: 99%